A rare case of ceruminous Syringocystadenoma papilliferum arising from the bony external auditory canal of an elderly patient - Faye Victoria C. Casimero; Ann Margaret V. Chang (Elsevier, 2020)
Syringocystadenoma papilliferum (SCAP) is an exceptionally rare benign adnexal neoplasm arising from the dermal ceruminous glands in the external auditory canal. Due to its lack of distinct clinical and radiologic features, definite diagnosis primarily relies on histopathologic examination after incisional or excisional biopsy. Only a handful of cases have been documented thus far. Herein, we report a case of SCAP in this unusual location. Existing literature regarding its clinical, radiographic and histomorphologic characteristics is reviewed. Keywords: Syringocystadenoma papilliferum, Ceruminous gland tumors, External auditory canal